Mediterranean diet adherence on self-concept and anxiety as a function of weekly physical activity: an explanatory model in higher education - Melguizo-Ibáñez, Eduardo; González-Valero, Gabriel; Badicu, Georgian; Yagin, Fatma Hilal; Alonso-Vargas, José Manuel; Ardigò, Luca Paolo; Puertas-Molero, Pilar (Frontiers in Nutrition, 2023)
Scientific literature has now demonstrated the benefits of an active lifestyle on people's psychological health. Based on the above statement, the aim is to (a) Evaluate and adjust a structural equation model containing the variables anxiety, self-concept and the Mediterranean diet adherence and (b) To contrast the proposed theoretical model by studying the differences between the variables according to the level of weekly physical activity in a sample of 558 university students. A non-experimental, exploratory, crosssectional investigation has been proposed.. Instruments such as the PREDIMED Questionnaire, the Beck Anxiety Inventory, the International Physical Activity Questionnaire and the Form 5 Self-Concept Questionnaire were used to collect data. Results show that students showing low adherence to the Mediterranean diet evidenced higher levels of anxiety (M=0.95) than those showing a high degree of adherence (M=0.75). It is also observed that a high degree of adherence to the Mediterranean diet reports higher scores in the different dimensions of self-concept compared to young people with a low degree of adherence. In conclusion, it is affirmed that young people who show a high degree of adherence to this dietary pattern show lower levels of anxiety and greater recognition of the different areas of self-concept.